2013
DOI: 10.1093/carcin/bgt170
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac inhibits pancreatic carcinogenesis in LSL-KrasG12D-LSL-Trp53R172H-Pdx-1-Cre mice via suppressing aldo-keto reductase family 1B10 (AKR1B10)

Abstract: Sulindac has been identified as a competitive inhibitor of aldo-keto reductase 1B10 (AKR1B10), an enzyme that plays a key role in carcinogenesis. AKR1B10 is overexpressed in pancreatic ductal adenocarcinoma (PDAC) and exhibits lipid substrate specificity, especially for farnesyl and geranylgeranyl. There have been no studies though showing that the inhibition of PDAC by sulindac is via inhibition of AKR1B10, particularly the metabolism of farnesyl/geranylgeranyl and Kras protein prenylation. To determine the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Sulindac (34) belongs to the indole acetic acids of NSAIDs and is also a potent competitive inhibitor of AKR1B10. It inhibits the occurrence of pancreatic cancer through suppressing K-ras protein prenylation by targeting AKR1B10 [48]. Consistent with the previous reports [81], sulindac has shown higher inhibitory potency against AR than AKR1B10, which might be illustrated by the two ordered and buried water molecules only existing in AKR1B10 and the different orientation and stacking interaction given by Phe122/Phe123 [Protein Data Bank (PDB) entry 4WEV] [32].…”
Section: Drugssupporting
confidence: 82%
See 1 more Smart Citation
“…Sulindac (34) belongs to the indole acetic acids of NSAIDs and is also a potent competitive inhibitor of AKR1B10. It inhibits the occurrence of pancreatic cancer through suppressing K-ras protein prenylation by targeting AKR1B10 [48]. Consistent with the previous reports [81], sulindac has shown higher inhibitory potency against AR than AKR1B10, which might be illustrated by the two ordered and buried water molecules only existing in AKR1B10 and the different orientation and stacking interaction given by Phe122/Phe123 [Protein Data Bank (PDB) entry 4WEV] [32].…”
Section: Drugssupporting
confidence: 82%
“…AKR1B10 has been shown to promote cell growth and survival via modulating lipid synthesis and membrane function by hindering the degradation of acetyl-CoA carboxylase-(ACCA), a rate-limiting enzyme in fatty acid synthesis, through the ubiquitination-proteasome pathway [45,46]. AKR1B10 is also involved in protein prenylation through the farnesyl pathway [38,47], a crucial event in carcinogenesis [14,48]. Taken together, these studies suggest that AKR1B10 may play an important role in the development and progression of cancers.…”
Section: Functions Of Akr1b10mentioning
confidence: 99%
“…ABCC1, ABCC3 and ABCC5 genes) are under Nrf2/ARE-mediated regulation, and increased expression of these transporters in PDAC is associated with a poor treatment response (Mohelnikova-Duchonova et al, 2013). The basal and inducible expression of several phase I and phase II drug detoxification enzymes by the Nrf2/ARE system is widely recognised, and over expression of aldo-keto reductase Li et al, 2013;Zhang et al, 2014;Yi and Oh, 2015), aldehyde dehydrogenase (Yi and Oh, 2015;Singh et al, 2015), and NQO1 (Awadallah et al, 2008) have been identified in several PDAC cell lines. Many of these drug-metabolizing enzymes as well as the antioxidant systems require NADPH as a cofactor, and Nrf2 regulates all four of the NADPH-generating enzymes.…”
Section: Cytoprotection By Are-driven Genesmentioning
confidence: 99%
“…Amongst well-and moderately differentiated pancreatic cancer specimens, approximately 70 per cent were found to over-expressed AKR1B10, compared to surrounding morphologically normal ducts . This Nrf2-target protein is of particular interest because its inhibition both impedes pancreatic carcinogenesis, and leads to a reduction in activated K-Ras protein (Li et al, 2013).…”
Section: Are-driven Gene Expression Is Increased In Pancreatic Cancermentioning
confidence: 99%
“…In the present study, TPA inhibited the A549 cell 418 growth whereas ERK was activated, and ERK-pathway inhibitor 419 U0126 reversed this effect. It is assumed that ERK may act as an press cell growth [10,11,30], suggesting that AKR1B10 itself may 428 be involved in the positive regulation of cell proliferation. AKR1B10 …”
mentioning
confidence: 99%